Study guides

☆☆

Q: Factor 3ab - a - 3b2 plus b?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)

(a+b)3=a3+b3+3ab(a+b) a3+b3=(a+b)3-3ab(a+b) a3+b3=(a+b)(a2-ab+b2)

(a+b)cube = a cube + b cube + 3a square b + 3ab square

5ab-2ab+4a-b+5b = 3ab+4a+4b

(a + b)(b + c)

Related questions

3ab - a - 3b2 + b = -3b2 + 3ab + b - a = -3b(b - a) + 1(b - a) = (1 - 3b)(b - a)

(3b - 1)(a - b)

(a+b)(3b+1)

Yes.

6

3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)

3a(b+c)+2b(b+c)

(3a - 2c)(b - d)

Factorizing 3ab + 3ac gives 3a (b + c).Factorizing is to express a number or expression as a product of factors.When factorizing always look for common factors. To factorize (3ab + 3ac) look for the highest factor between the two terms (3a). 3ab + 3ac = 3a (b + c)

(a+b)3=a3+b3+3ab(a+b) a3+b3=(a+b)3-3ab(a+b) a3+b3=(a+b)(a2-ab+b2)

It is an algebraic expression because it has no equality sign.

(a+b)cube = a cube + b cube + 3a square b + 3ab square

People also asked

Featured Questions